Participation in the Innovation Laboratory in Nursing: awarding of an experience in Ceará (Research, Society and Development, 2022)
This study aimed to report the professional experience in the Innovation Laboratory in Nursing, promoted by the Pan-American Health Organization in partnership with the Brazilian Federal Council of Nursing, which had as one of the finalist experiences the “Implementation of the Intraoperative Blood Salvage Technique in a public trauma care service in Ceará, Brazil”. This is a descriptive study of the experience report type. The experience process at the Innovation Laboratory sought to value and strengthen Universal Health – registrations on September 23, 2019, ending on December 9, 2020. As results, the experience was developed in six stages and post-stages, namely: launching and registration; disclosure of selected experiences; seminar to present selected experiences; on-site technical visit; disclosure of finalist experiences; ceremony of recognition of the finalist experiences; and presentation at the 23rd Brazilian Congress of Nursing Councils and text publication in the Journal “Enfermagem em Foco”. In this perspective, the on-site technical visit stands out, as it enabled the evaluators to have contact with the technique procedure in the operating room through realistic simulation, with emphasis on urgent and emergency thoracoabdominal trauma and chest drainage procedures. Thus, it is concluded that participating in the Innovation Laboratory allowed sharing experiences on the Intraoperative Blood Salvage Technique, aimed at promoting its replicability in other scenarios.